2021
DOI: 10.1038/s41557-021-00735-w
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity control in hydrogenation through adaptive catalysis using ruthenium nanoparticles on a CO2-responsive support

Abstract: With the advent of renewable carbon resources, multifunctional catalysts are becoming essential to hydrogenate selectively biomass-derived substrates and intermediates. However, the development of adaptive catalytic systems, that is, with reversibly adjustable reactivity, able to cope with the intermittence of renewable resources remains a challenge. Here, we report the preparation of a catalytic system designed to respond adaptively to feed gas composition in hydrogenation reactions. Ruthenium nanoparticles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 48 publications
2
51
0
2
Order By: Relevance
“…[3] These methods typically rely on varying a parameter such as catalyst, [4] ligand [5] or reagent. [6] As a non-invasive stimulus which offers excellent spatialtemporal control, light would be particularly attractive to control selectivity. [7] However, despite the rapidly growing interest in photochemical methods, light is still most often used to promote reactions that either take place very slowly, or cannot occur at all in the dark.…”
mentioning
confidence: 99%
“…[3] These methods typically rely on varying a parameter such as catalyst, [4] ligand [5] or reagent. [6] As a non-invasive stimulus which offers excellent spatialtemporal control, light would be particularly attractive to control selectivity. [7] However, despite the rapidly growing interest in photochemical methods, light is still most often used to promote reactions that either take place very slowly, or cannot occur at all in the dark.…”
mentioning
confidence: 99%
“…The synthetic potential of such controlled transformations can help to exploit the green chemistry principles for the existing chemical value chain as well as for novel biomass-derived product streams. ,,,,, Recently demonstrated examples that are very challenging to achieve with classical heterogeneous or homogeneous catalysts include the selective hydrogenation of bicyclic heteroaromatics, fluorinated aromatics, aryl ether cleavage, and hydrogenation and deoxygenation of side chains in aromatics. Most recently, it has been demonstrated that the introduction of reactive functional groups can open the path to adaptive catalytic systems enabling reversible control over their performance by applying external stimuli . The manifold opportunities arising from the emerging design criteria motivate future developments in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, it has been demonstrated that the introduction of reactive functional groups can open the path to adaptive catalytic systems enabling reversible control over their performance by applying external stimuli. 62 The manifold opportunities arising from the emerging design criteria motivate future developments in this direction.…”
Section: Reactivity: Activation Of Dihydrogen For the Conversion Of U...mentioning
confidence: 99%
“…[220] Angewandte Chemie AufsĂ€tze redox catalysis, there are also other potentially metal-free approaches that may be investigated in the context of polymer upcycling. These could include organocatalyzed CÀ H functionalization methods, [221][222][223] aerobic CÀ H functionalization strategies that use molecular O 2 as a sustainable oxidant in place of metal catalysts, [224] metal-free electrochemical oxidative CÀ H trifluoroalkylations, [225][226][227] and biocatalytic methods that employ artificial enzymes for direct and selective CÀ H functionalization. [228,229] This list is not exhaustive and many new methodologies emerging from the field of organic synthesis can conceivably be applied to polymer upcycling, though the efficacy of such reactions on polymers will remain an open question until further investigations can be carried out.…”
Section: Polymer Upcycling Via Organocatalyzed And/or Transition-meta...mentioning
confidence: 99%